Knowledge regarding assessment of sepsis among Greek nurses. Issue 2 (March 2014) - Stamataki, P; Papazafiropoulou, A; Kalaitzi, S; Sarafis, P; Kagialari, M; Adamou, E; Diplou, A; Stravopodis, G; Papadimitriou, A; Giamarellou, E; Karaiskou, A; ,
The aim of the present survey was to evaluate nurses' knowledge regarding sepsis in Greece. A total of 835 registered nurses (125 males/710 females) from tertiary hospitals in Greece were interviewed from April 2008 to December 2009. All participants completed a self-completed questionnaire about assessment of sepsis (see Figure 1). Basic demographic information was recorded. The protocol and questionnaire were approved by the Ethics Committees of participating hospitals. The majority of the participants answered correctly regarding awareness of systemic inflammation – 83.5% regarding the role of temperature in the definition of systemic inflammation; 81.3% regarding the importance of white blood cell count; and 49.9% and 46.3% regarding the role of tachycardia and tachypnoea, respectively. The same pattern was observed regarding the answers about the assessment of sepsis – 79.4% of the nurses answered correctly about the role of blood pressure; 70.9% about the role of urine volume; and 43.5% about the importance of oxygen saturation. Finally, 57.2% of the participants confirmed that in practice they followed the current guidelines for the diagnosis and treatment of patients with sepsis. The study has established baseline data with which future studies can be compared.